2019
DOI: 10.9734/jeai/2019/v34i230168
|View full text |Cite
|
Sign up to set email alerts
|

Pruning Intensity and Lopping System in Fig Plants in the Brazilian Semiarid Region

Abstract: Aims: Fig plants produce fruits in branches of the year, which grow after emission of buds from the leaf armpits. And the lopping system is one of the most common practices among the green fig farmers to increase production. Thus, the present work aimed to improve the physical, chemical and productive characteristics of fig trees in the semiarid region of Brazil. Study Design: A complete randomized block design was used in a 3x2 factorial scheme (three pruning intensities: 5, 10 and 15 cm in length; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…An increasing trend in total soluble solids was observed with increasing levels of pruning in figs, which was consistent with the results of pruning intensity on Poona cultivar fig and guava trees (Adhikari and Kandel, 2015;Chaudhari and Desai, 1996). The titratable acidity contents were similar to the reports of Silva et al (2019), who found that TA contents ranged from 0.20% to 0.23% when the trees were pruned (Silva et al, 2019). Early ripening fruits have two benefits.…”
Section: Discussionsupporting
confidence: 85%
“…An increasing trend in total soluble solids was observed with increasing levels of pruning in figs, which was consistent with the results of pruning intensity on Poona cultivar fig and guava trees (Adhikari and Kandel, 2015;Chaudhari and Desai, 1996). The titratable acidity contents were similar to the reports of Silva et al (2019), who found that TA contents ranged from 0.20% to 0.23% when the trees were pruned (Silva et al, 2019). Early ripening fruits have two benefits.…”
Section: Discussionsupporting
confidence: 85%